Optimum injection dose rate of hydrogen sulfide scavenger for treatment of petroleum crude oil - T.M. Elshiekh; H.A. Elmawgoud; S.A. Khalil; A.M. Alsabagh (Egyptian Journal of Petroleum)
Hydrogen sulfide H2S scavengers are chemicals that favorably react with hydrogen sulfide gas to eliminate it and produce environmental friendly products. These products depend on the type and composition of the scavenger and the conditions at which the reaction takes place. The scavenger should be widely available and economical for industry acceptance by having a low unit cost. The optimum values of H2S scavenger injection dose rate of scavenging hydrogen sulfide from the multiphase fluid produced at different wells conditions in one of the Petroleum Companies in Egypt were studied. The optimum values of H2S scavenger injection dose rate depend on pipe diameter, pipe length, gas molar mass velocity, inlet H2S concentration and pressure. The optimization results are obtained for different values of these parameters using the software program Lingo. In general, the optimum values of H2S scavenger injection dose rate of the scavenging of hydrogen sulfide are increased by increasing of the pipe diameter and increasing the inlet H2S concentration, and decreased by increasing the pipe length, gas molar mass velocity and pressure.